Le travail et la « vie psychotique » - Pascale Molinier; Marie-Christine Pheulpin (Perspectives Interdisciplinaires sur le Travail et la Santé)
This article adopts approaches employed in the field of psychodynamics of work and psycho-pathology. It is built on a dialogue between psychological health and illness on the one hand, and pleasure and suffering at work on the other. In the current French context, media and social actors frequently compare a mental health event, when it is connected with signs of suffering at work, with the subject’s “normality” before this suffering began. Work is thus judged to be the “sole” cause of the person’s psychological problems. This mechanical model neglects the complexity of the relations between work and psychological balance. It overlooks those lives that we designate here as being “penetrated by psychosis” and thus ignores the vulnerability of the human psyche and of people who do not easily fit into normal standards. This article highlights the significance of the symbolic resonance between one’s unconscious psychological life and work life. It likewise criticizes the importance currently attributed to the concept of recognition, and thus to the social world and other externals, without taking into account internal sources of satisfaction.